(untitled) (Quinto Sol, 2017)
In this article we will analyze, firstly, the ideas on totalitarianism held by a group of Catholic traditionalists who served between the decades of 1960 and 1980 and who recognized themselves as experts in educational and University issues. Secondly, we will describe what kind of school they defended and who were considered the main adversaries to the model proposed. We will depart from the study of the book by Antonio Caponnetto called Pedagogía y Educación published during the last dictatorship (1981) and we will show how Caponnetto and other traditionalists criticized the main topics about the new pedagogy, the educator Paulo Freire, the referents of UNESCO and the psychology of Jean Piaget. In the last part of this paper, we will present the diagnosis they made about education and more specifically about the elementary level and the teaching of courses in high school.